Bio Diversity and Density of Phytoplankton in Pond of Kirtipur - Kushwaha, Pramod Kumar (Academic Voices: A Multidisciplinary Journal, 2013)
The density of the phytoplankton during the study period was recorded 1420112 No. / L with the average value of 100150.3 No. / L fortnightly. All the four groups of phytoplankton were noted with low diversity of only 12 genera. The maximum density was found on 16th June 1992 (summer period) and the minimum on 25th Dec. 1991 (winter period). Among the four major groups, Chrysophyta (Bacillariophyceae) constituted 42.1 % followed by Cyanophyta (Myxophyceae) 32.6% , pyrrophyta (Desmidaceae) 18.5% and Chlorophyta (Chlorophyceae) 6.8% respectively. The free CO2 was positive coefficient value of phytoplankton in relation to temp., PH but dissolved oxygen had negative value of coefficient correlation. Academic Voices, Vol. 2, No. 1, 2012, Pages 43-47 DOI: http://dx.doi.org/10.3126/av.v2i1.8285